2008
DOI: 10.1890/07-2038.1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide and Methane Fluxes in Drained Tropical Peat Before and After Hydrological Restoration

Abstract: Present tropical peat deposits are the outcome of net carbon removal from the atmosphere and form one of the largest terrestrial organic carbon stores on the Earth. Reclamation of pristine tropical peatland areas in Southeast Asia increased strikingly during the last half of the 20th century. Drainage due to land-use change is one of the main driving factors accelerating carbon loss from the ecosystem. Dams were built in drainage-affected peatland area canals in Central Kalimantan, Indonesia, in order to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
149
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 24 publications
12
149
1
4
Order By: Relevance
“…In general, the results of CH 4 emission reduction followed by methane consumption fully agree with those of other studies that evaluated the effect of lowering the water-table level by draining in flooded soils in several parts of the world Nykanen et al, 1995;Maljanen et al, 2004;von Arnold et al, 2005;Furukawa et al, 2005;Bridgham et al, 2006;Elder & Lal, 2008;Jauhiainen et al, 2008;Jiang et al, 2009;Huang et al, 2010;Page & Dalal, 2011). All these authors showed that small water-table decreases cause drastic reductions in methane emissions, demonstrating the strong effect of drainage on CH 4 fluxes.…”
Section: In Drained Histosolssupporting
confidence: 87%
See 2 more Smart Citations
“…In general, the results of CH 4 emission reduction followed by methane consumption fully agree with those of other studies that evaluated the effect of lowering the water-table level by draining in flooded soils in several parts of the world Nykanen et al, 1995;Maljanen et al, 2004;von Arnold et al, 2005;Furukawa et al, 2005;Bridgham et al, 2006;Elder & Lal, 2008;Jauhiainen et al, 2008;Jiang et al, 2009;Huang et al, 2010;Page & Dalal, 2011). All these authors showed that small water-table decreases cause drastic reductions in methane emissions, demonstrating the strong effect of drainage on CH 4 fluxes.…”
Section: In Drained Histosolssupporting
confidence: 87%
“…These processes are regulated by oxygen (O 2 ) supply and availability of labile carbon (C), being methanogenesis predominant under anaerobic conditions. The CH 4 flux in waterlogged areas is controlled by soil properties and processes (Roulet & Moore, 1995;Whalen, 2005;Jauhiainen et al, 2008), by microbiological factors (Le Mer & Roger, 2001;Kögel-Knabner et al, 2010;Page & Dalal, 2011), climatic factors (von Arnold et al, 2005;Dalal & Allen, 2008;Jiang et al, 2009), vegetation Koh et al, 2009) and land management (Elder & Lal, 2008;Huang et al, 2010). Precipitation and air temperature are important climatic factors that can affect soil CH 4 emissions, although with great variability (Le Mer & Roger, 2001;Whalen, 2005;Dalal & Allen, 2008;Koh et al, 2009;Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one of the most important peatland restoration measures is blocking of drainage canals by dams and thus raising the groundwater level of the surrounding peatland. Damming activities performed in the former Mega Rice Project area, in Sebangau National Park and in Merang peatland of South Sumatra have shown that the water retention upstream of dams could be increased thereby decreasing peat desiccation during the dry season (Suryadiputra et al 2005;CKPP 2008;Jauhiainen et al 2008). Few rehabilitation attempts have been undertaken in the past , however within the context of ongoing discussions concerning climate change tropical peatlands have now been recognised as major sources of greenhouse gas emissions (Rieley and Page 2005;Hooijer et al 2006;Uryu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Jauhiainen et al 2005) and disturbed (e.g. Hirano et al 2007;Jauhiainen et al 2008) conditions are needed for estimation of gas emissions with potentially global consequences. However, the results of small-scale studies cannot be reliably propagated to the regional level without large-scale high spatial resolution assessments of the overall status of degradation and development in the peatland areas.…”
Section: Introductionmentioning
confidence: 99%